Знахідки І тис. н. е. у Полтавському Поворсклі: за матеріалами робіт 2016 р. - Володарець-Урбанович, Я.В.; Пуголовок, Ю.О.; Щербань, А.Л. (Археологія, 2018)
Випадкові знахідки другої — третьої чверті І тис. н. е. біля сс. Велика Рублівка, Драни, Устименки та смт Опішне, виявлені у 2016 р. місцевими мешканцями та передані на зберігання до фондів КУ ІКЗ «Більськ» та Національного музею-заповідника українського гончарства в Опішному вводяться у науковий обіг. Серед них фрагменти фібул, люстерка, деталь замка скриньки та уламки ліпленого посуду. The article deals with the finds of the second and third quarters of 1st millennium CE, which were found and transferred by local residents from the villages Velyka Rublivka, Drany, Ustimenki and Opishnia. The finds are fibulae, mirrors, a detail of the chest lock and fragments of pottery. The upper shield plate of the Eastern European emaciated enamel fibula (fig. 1, 1; 2, 1) — re-folded / a crossbar, type II according to G.F. Korzukhina, or T-shaped type with triangular or cruciform legs, the developed phase, seria 2, type II, according to E.L. Gorokhovskyi, in the vicinity of Velyka Rublivka village was discovered. The three-fingered fibula from the village Drany (fig. 1, 2; 2, 2) refer to the transitional type from the lamellar to the palatine types. The fragments of two mirrors (fig. 1, 4, 5; 2, 4, 5) from Ustimenky belong to the Sarmatian time and find the wide analogies among the Sarmatian burials of the Northern Black Sea Coast and the Crimea. Also, the detail of the chest lock or the clamp of the provincial-Roman type (fig. 1, 3; 2, 3), although there are similar finds on the Cherniakhiv culture sites. The Penkivka culture settlement near the Rag doll museum in Opishnia was also discovered. В статье публикуются находки I тыс. н. э. (вторая и третья четверть), которые был выявлены и переданы местными жителями из с. Великая Рублевка, Драны, Устименки и пгт Опошня. Находки представлены фибулами, зеркальцами, деталью замка сундука и обломками керамики. В частности, в окрестностях с. Великая Рублевка обнаружен верхний щиток фибулы круга восточноевропейских варварских выемчатыми эмалей (рис. 1, 1; 2, 1) — перекладчастые по Г.Ф. Корзухиной, тип II или Т-образных с треугольными или крестообразными ножками развитой фазы по Е.Л. Гороховскому, вторая серия, тип II. Трехпальчатая фибула из с. Дранов (рис. 1, 2; 2, 2) относится к переходному типу от двопластинчатых к пальчатых. Обломки двух зеркалец (рис. 1, 4, 5; 2, 4, 5) с Устименок относятся к сарматскому времени и находят широкие аналогии среди сарматских погребений Северного Причерноморья и Крыма. Так же и деталь запора (скобы) замка провинциально-римского типа от сундука (рис. 1, 3; 2, 3), хотя есть похожие находки и на черняховских памятниках. Также на усадьбе музея куклы-мотанки в пгт Опошня (рис. 9) выявлено поселения пеньковской культуры.